Media Capitalism on Religious Radio in West Java - Basith, Achmad Abdul; Hidayat, Dadang Rahmat (Jurnal Kajian Jurnalisme, 2026)
Background: The development of the internet has now shifted the function of radio as a mass media. However, radio still has loyal listeners, especially for content with more specific segmentation. This condition has encouraged radio stations to create new strategies by changing their names and broadcast formats to better suit their target audiences. One example is religious-themed broadcasts or religious radio. In a case study in West Java, the West Java Regional Indonesian Broadcasting Commission (KPID) found that, as of January 2025, there were 33 religious radio stations in the region. Purpose: This study aims to reveal the dynamics of religious radio in West Java from a political economy perspective. Methods: The researchers used qualitative methods to gather information through open discussions and direct interviews. Results: The findings show that there is a process of commodification in the form of commercialization of broadcasts and audiences, followed by a process of structuration marked by the restriction of women’s voices in radio broadcasts, exclusivity of content, and violations of formal regulations (the obligation to play the Indonesian national anthem, Indonesia Raya), to a process of spatialization as evidenced by the diversification of religious-themed products for media expansion. Conclusion: The above case study shows that religious radio exists not only as a community medium but also as a form of business, political, and social competition among capitalists. Implications: The results of this study provide a new comprehensive understanding of the dynamics of religious radio, from its presence as an information medium to its role as a vehicle for capitalist business.